New formulation of Bacillus thuringiensis israelensis for the control of Culex quinquefasciatus Say, 1823 (Diptera, Culicidae) in an effluent treatment pond - Bocaleti, Alex da S.; Almeida, Valtir Y. T. de; Lima, Eduarda A. de; Schorr, Renan R.; Marques, Francisco de A.; Silva, Mario A. N. da; Vilas-Boas, Gislayne F. L. T.; Zequi, João A. C. (BioAssay, 2024)
Culex quinquefasciatus Say, 1823 (Diptera, Culicidae) has relevance in health due to their role in transmitting pathogens that cause diseases such as Bancroftian filariasis, West Nile virus, Rift Valley fever, Saint Louis encephalitis, Zika virus and Mayaro virus. Subsequent monitoring and control of these vectors are crucial to minimize the circulation of these pathogens. Bacillus thuringiensis subspecies israelensis de Barjac, 1978 (Bti) is a bacterium that produces toxins with specific entomopathogenic action, distinguishing it from synthetic insecticides due to its high specificity and lower susceptibility to resistance. This study aims to evaluate the effectiveness of new Bti-based formulations for controlling C. quinquefasciatus mosquitoes under field conditions. Product BR 101 demonstrated satisfactory efficacy for up to five days, achieving a peak population reduction of 94.97% on the third day post-application, followed by a gradual population recovery. The product proved effective for C. quinquefasciatus control without affecting abiotic factors, offering an efficient option for reducing vector density with minimal impact on non-target fauna due to its selectivity.